Book reviews - Sian Beavers; Andrew Brasher; Alison Buckler; Franscisco Iniesto (Journal of Interactive Media in Education, 2016)
The following publication contains book reviews of these titles:- Seth Giddings, (2014) Gameworlds: Virtual Media and Children’s Everyday Play. New York: Bloomsbury Academic. 192 pages. ISBN-10: 1501318292. ISBN-13: 978-1501318290.- Gibbons, A. S. (2014). An architectural approach to instructional design. New York: Routledge. ISBN-10: 0415807395. ISBN-13: 978-0415807395.- Simone White and Michael Corbett (eds.), 2014. Doing Educational Research in Rural Settings: Methodological issues, international perspectives and practical solutions. Routledge: London and New York. 234 pages ISBN-10: 041582351X, ISBN-13: 978-0415823517.- Jill Porter (2014). Understanding and Responding to the Experience of Disability. Routledge: London and New York. 170 pages ISBN-10: 0415822912 ISBN-13: 978-0415822916.